Investigation on Corrosion Behaviour of LM25-SiCp Composite Using Taguchi Method - R. Suresh Kumar; S. Senthil Kumar; C. Rajendran; Samson Jerold Samuel Chelladurai; Gizachew Balcha (Advances in Materials Science and Engineering, 2022)
The aim of this investigation is to optimize the process parameters to obtain minimum corrosion rate and weight loss of Al/SiCp metal matrix composites. A Taguchi based grey relation analysis was carried out. The process parameters such as number of hours dipped in 3% NaCl solution, vol.% of SiCp and aging at 170°C for hours were considered. The working range of each process parameters were fixed based on minimum weight loss and low corrosion rate. The test was carried out using Taguchi based grey relationship analysis. Three factor three level L9 orthogonal array was used and output responses such as weight loss and corrosion rate were calculated. Based on the grey relationship analysis, the rank of each process parameters was calculated. Based on the F value, the vol. % of SiCp (38.42%) on the metal matrix composite followed by number of hours samples immersed in 3% NaCl solution (35.3%) and aging at 170°C for hours (25.78%) were found as influencing parameters on corrosion rate and weight loss. The surface of corroded samples was investigated and reported.